Perspectives and Challenges for the Adoption of b-learning Practices in the Context of a HEI in Angola (Indagatio Didactica, 2025)
Despite the expansion and growing integration of Information and Communication Technologies (ICT) within the knowledge society, their impact in the field of education has not yet been proportional. Blended learning (b-learning) emerges as an innovative proposal that combines the best of face-to-face and online interactions in order to promote new possibilities for teaching and learning. This study aims to understand the perspectives and challenges faced by the government, the institutional presidency, teachers, and students of a Higher Education Institution (HEI) regarding the integration of b-learning into the educational process. Methodologically, a qualitative approach was adopted, based on a case study. The participants included the president of the HEI, five ICT teacher trainers, twelve lecturers, and twenty-one students. Data were collected through documentary analysis and focus groups, and subsequently analysed using content analysis techniques. The findings revealed that the government, institutional leadership, teachers, and students hold a favourable view towards the adoption of b-learning within the educational system. However, they also highlight a misalignment between governmental policies and the actual conditions of HEIs for implementing b-learning, evidenced by technological infrastructure and technical support deficiencies, curricular limitations, a lack of initial and ongoing teacher training in Digital Technology, and insufficient knowledge of appropriate pedagogical models for integrating b-learning. It is concluded that the effectiveness of b-learning requires alignment between infrastructure, curriculum, pedagogical models, and teacher training, taking into account Angola’s specific context. The flipped classroom stands out as a viable strategy, mitigating technological constraints and promoting pedagogical flexibility.
Keywords: higher education institution; b-learning; b-learning adoption factors